2021
DOI: 10.1021/acsami.1c20609
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Topotactic Host Composite Anode Toward Transparent Flexible Potassium-Ion Microcapacitors

Abstract: Transparent flexible supercapacitors (TFSCs) are a tantalizing power supplier for future transparent flexible electronics. However, their energy density is far behind a practical level while maintaining high transparency. We report here a transparent flexible potassium-ion microcapacitor, and its high energy density (15.5 μWh cm −2 ) roots in the battery-supercapacitor hybrid storage mechanism and much enlarged working voltage (3 V), outperforming the state-of-the-art TFSC, which is generally based on an aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Preparation of Quasi-Gel-Polymer-Electrolyte: The quasi-gel-polymerelectrolyte could be prepared based on previous reports. [67][68][69] Typically, 0.8 g polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) and 0.04 g polyethylene oxide (PEO) were mixed with acetone (10 mL) and ethanol (2 mL). The mixture was stirred at 60 °C for 6 h until it becomes a transparent gel.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Preparation of Quasi-Gel-Polymer-Electrolyte: The quasi-gel-polymerelectrolyte could be prepared based on previous reports. [67][68][69] Typically, 0.8 g polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) and 0.04 g polyethylene oxide (PEO) were mixed with acetone (10 mL) and ethanol (2 mL). The mixture was stirred at 60 °C for 6 h until it becomes a transparent gel.…”
Section: Supporting Informationmentioning
confidence: 99%
“…[42,[112][113][114] Bai et al reported an in situ hydrothermal method to synthesize materials (TF-PIMCs) with a stable tunnel structure by combing 1D K 2 Ti 6 O 13 nanobelts with quasi-2D graphite nanosheets (Figure 14a). [111] A successful proposal has been made for a multidimensional topotactic host composite anode. This anode utilizes a topotactic potassium-ion intercalation mechanism, resulting in superior rate performances and cycling stability for both gravimetric and volumetric measurements (Figure 14b).…”
Section: Titanium-based Materialsmentioning
confidence: 99%
“…Figure 14. a) Fabrication procedures, electrodes, and energy storage mechanism of TF-PIMCs. b) Gravimetric rate performances of the KTO/graphite anode.Reproduced with permission from Ref [111]…”
mentioning
confidence: 99%